Effects of supplementation with rumen-protected methionine on growth, feed efficiency, blood parameters, and health of weaned Holstein growing calves (Journal of Advanced Veterinary and Animal Research, 2026)
Objective: This study evaluated the effects of dietary supplementation with rumen-protected methionine (RPM) on growth performance, feed efficiency (FE), blood parameters, and health status in post-weaning calves. Materials and Methods: Forty weaned calves were randomly allocated to four groups: G1. No RPM supplementation (control); G2. RPM supplementation for 10 days post-weaning (days 75–85); G3. RPM supplementation for 20 days post-weaning (days 75–95); G4. RPM supplementation for 30 days post-weaning (days 75–105). Ethyl cellulose-coated D-L methionine was administered at 2 gm/day/calf. Growth performance, FE, serum biochemical parameters, complete blood count (CBC), and health indicators were investigated. Results: G4 showed the highest weight gain (1.01 kg/day) and FE (0.54), as well as the lowest feed conversion ratio (FCR) (1.84) (p < 0.05). In contrast, G1 had the lowest weight gain (0.82 kg/day) and FE (0.51), along with the highest FCR (1.98) (p < 0.05). RPM supplementation significantly reduced blood urea nitrogen, aspartate aminotransferase, and alanine aminotransferase levels (p < 0.05) but had no significant effect on total protein, triglyceride, or cholesterol levels. Additionally, it increased RBC count and hemoglobin concentration (p < 0.05), while WBC counts, lymphocytes, and platelets remained unaffected. Moreover, RPM supplementation significantly improved overall health and reduced the incidence of diarrhea (p < 0.05). Conclusion: Dietary supplementation with RPM had a positive influence on growth performance, FE, blood parameters, and overall health in growing calves. A daily dose of 2 gm/day/calf is recommended.J. Adv. Vet. Anim. Res., 12(4): 1192–1200, December 2025http://doi.org/10.5455/javar.2025.l979